Study of Distributions Encountered in forest Sampling - Mokashi, V. K.; Acharya, D. P. (Indian Forester, 1967)
Distributions arising out of sampling a forest area by treating small sized plots as sampling units are studied. It is observed that the number of trees in bigger girth classes follow a negative binomial distributlon for small plots as sampling units. The effects of Such distribution are indicated. However the case discussed here is limited to a particular forest and plot size. Further studies are needed to confirm these findings. Various distributions call for further probe under different forest conditions. Such studies are in progress.